Distributed Sensor Calibration with Minimum Connections in Wireless Sensor Networks - (:unkn) unknown (IEEE, 2017)
Nowadays, with the increasing number of application areas of wireless sensor networks, the need for an effective solution to the calibration problem in these networks has become increasingly apparent. In particular, considering the size of the network, accessing the entire network can be costly and/or access to all may not be possible. In this paper, the problem of consensus based distributed calibration has been studied for wireless sensor networks. In the proposed consensus based distributed algorithm, we first introduce the concept of leader sensors. Using this definition, we determine the set of sensors with minimum elements required for calibration of a given wireless sensor network. Finally, we illustrate the performance of the proposed method via simulations.
Keywords: wireless sensor networks; sensor calibration; distributed consensus; graph theory; CLOCK SYNCHRONIZATION